THE EFFECT OF USING PLEASE (PICK-LIST-EVALUATE-ACTIVATE-SUPPLY-END STRATEGY) ON STUDENTS ACHIEVEMENT IN WRITING DESCRIFTIVE TEXT AT SEVENT GRADE OF Mts NURUL HAKIM TEMBUNG - Nasution, Neni Fitriani (Faculty of Tarbiyah nad Teacher Training, 2021)
The purpose of this study was to determine the significant effect of the PLEASE (Pick-List-Evaluate-Activate-Supply-End) Strategy on student achievement in writing descriftive text in class VII Mts Nurul Hakim Tembung. This research used quantitative research with experimental design. The implementation was in class VII Mts Nurul Hakim Tembung. The researcher took 64 students consisting of 32 students for the experimental class and 32 students for the control class. In collecting the data, the researcher used test in essay test.. The researcher used two tests, the pre-test was given before the treatment and the post-test was given after the treatment in the learning process. Then the researchers analyzed the data using statistical formulas and Microsoft Excel 2010 with a significance level of 0.05. After analyzing the data, the researcher found that the value of tobserved was higher than the ttable. This can be seen from the tobserved (4.473)> t table (1.6) at the significance level of 0.05 and degrees of freedom (df) 62.It means that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can be concluded that the PLEASE (Pick-List-Evaluate-Activate-Supply-End) strategy has significant effect on students’ writing achievement in descriftive text of seventh grade students at Mts Nurul Hakim Tembung. This is related to the results of observations which show that students are more interested and motivated in attending classes and enthusiastic during the teaching and learning process so that their descriptive writing achievement increases. Keyword: PLEASE starategy, Students’achievement , writing descriptive text